Elements of Comparative Syntax: Theory and Description - Aboh, Enoch; Haeberli, Eric; Puskás, Genoveva; Schönenberger, Manuela (De Gruyter, 2017)
Generative Syntax; Comparative Syntax; Micro-comparative Syntax